Habitation of Clean and Healthy Living Behavior in Preventing COVID-19 AT AL-Husna Marindal Islamic Boarding School - Natassa, Siska Ella; Siregar, Darmayanti; Armidin, Ranu Putra (Talenta Publisher, 2022)
Clean and healthy living behavior (PHBS) is essentially aimed at increasing public awareness to want to live a clean and healthy life. PHBS in educational facilities should be prioritized considering that children have returned to school during the new normal period of the corona virus (Covid-19) pandemic. According to the WHO, washing hands with soap and water or using an alcohol-based hand rub can kill the COVID-19 virus. Good hand washing is the first line of defense against the spread of many diseases. Hand washing can help prevent the spread of illnesses ranging from the common cold to more serious infections. Prevention of coronavirus disease also comes from good immunity. In addition to adequate nutritional intake, oral health is also needed to obtain a healthy immune system. The oral cavity is a part of the body that functions as a pathway for food and drink to enter the body and plays a role in increasing immunity. On the other hand, it is also the 'entrance' for various pathogens that cause infection. Therefore, community service for children is needed in the form of habituation efforts to wash hands and brush teeth properly. The purpose of this service is to improve the health status of children by building hand washing and toothbrushing facilities as an effort to habituate clean and healthy living behavior in preventing the spread of the Covid-19 disease. It is hoped that with the dedication carried out, there will be changes in behavior and improvement of health in children at school.